Composition and decomposition of ontologies - Simões, Dora
This paper proposes a new method for managing the use of ontologies in the context of a Collaborative Networks. Firstly, an overview of the process of ontology composition and decomposition is given and the ontology library system adopted described. Then, the ontologies' ranking and classification method is described, explaining a set of metrics inspired in social network approaches. Finally, the results of preliminary tests are discussed.